A systematic review of shared visualisation to achieve common ground. (June 2015) - Yusoff, Nor'ain Mohd; Salim, Siti Salwah
Abstract: This paper reports a systematic review of shared visualisation based on fifteen papers from 2000 to 2013. The findings identified five shared visualisation strategies that represent the ways implemented to process data sharing and knowledge to arrive at the desired level of understanding. Four visualisation techniques were also identified to show how shared cognition is made possible in designing tools for mediating data or knowledge among the users involved. These findings provide research opportunities in integrating rich interactive data visualisation for mobile-based technologies as an effective mean in supporting collaborative work. Finally, social, task and cognitive elements which can be significantly supported by shared visualisation and a guideline for future researchers seeking to design shared visualisation-based systems are presented. Highlights: We conducted a systematic review of shared visualisation for shared cognition. We have identified 9 shared visualisation strategies and techniques. These strategies, techniques are capable to provide social, task, cognitive support. The findings of this review suggest a guide for shared visualization design.